2014
DOI: 10.1152/ajprenal.00247.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diabetic nephropathy by compound 21, selective agonist of angiotensin type 2 receptors, in Zucker diabetic fatty rats

Abstract: The aim of this study was to evaluate the effect of compound 21 (C21), a selective AT 2 receptor agonist, on diabetic nephropathy and the potential additive effect of C21, when associated with losartan treatment, on the development of albuminuria and renal fibrosis in Zucker diabetic fatty (ZDF) rats. The experiments lasted 15 wk (from 5 to 20 wk of age) and were performed in 40 ZDF rats and 12 control lean rats. ZDF rats were divided into 4 groups: 1) 9 rats were treated with losartan; 2) 10 rats were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
6
29
1
Order By: Relevance
“…Together, these data suggested that the lack of AT 2 R might not interrupt the sequence of the final nephron formation, but instead modify the maturation, integrity, and function of specialized renal cells, such as podocytes. In line with the observations that AT 2 R enhanced the expression of slit diaphragm molecules [40] and AT 2 R had a renoprotective effect to prevent diabetic nephropathy occurring in Zucker rats [41], we found that several podocyte markers, such as p57, WT-1, nephrin, and Synpo expression, were significantly decreased in the glomeruli of AT 2 RKO mice at 3 weeks of age that had a detectable amount of albumin leakage in their urine. Together, these data underscore the functional role of AT 2 R in podocyte formation and integrity.…”
Section: Discussionsupporting
confidence: 90%
“…Together, these data suggested that the lack of AT 2 R might not interrupt the sequence of the final nephron formation, but instead modify the maturation, integrity, and function of specialized renal cells, such as podocytes. In line with the observations that AT 2 R enhanced the expression of slit diaphragm molecules [40] and AT 2 R had a renoprotective effect to prevent diabetic nephropathy occurring in Zucker rats [41], we found that several podocyte markers, such as p57, WT-1, nephrin, and Synpo expression, were significantly decreased in the glomeruli of AT 2 RKO mice at 3 weeks of age that had a detectable amount of albumin leakage in their urine. Together, these data underscore the functional role of AT 2 R in podocyte formation and integrity.…”
Section: Discussionsupporting
confidence: 90%
“…In concordance, C21 improved albuminuria through the prevention of renal inflammation and production of NO and cGMP in STZ-induced male SpragueDawley rats (73). In T2DM, C21 treatment in combination with losartan showed an additive effect on reducing albuminuria and slowing the progression of nephropathy in male Zucker diabetic fatty rats (14). Acute C21 administration improved renal function in female, but not in male, spontaneously hypertensive (SHR) rats.…”
Section: Sex Differences On Ras Blockade In Diabetic Nephropathymentioning
confidence: 95%
“…AT 2 R also has anti-inflammatory and antioxidative functions in the kidney in obese Zucker rats but proinflammatory and pro-oxidative functions in lean Zucker rats (895). An AT 2 R agonist may also prevent diabetic nephropathy through a similar mechanism (130,513). However, there are certain limitations in these studies such as specificity issues of pharmacological AT 2 R agonists/antagonists and the AT 2 R antibody utilized.…”
Section: E At 2 R In Renal Physiologymentioning
confidence: 99%